Navigating Challenges in the Just Energy Transition: Policy and Institutional Dynamics for Implementation in North Macedonia - Antonovska Joskoska, Frosina; Bitrakov, Konstantin (Institute for Sociological, Political and Juridical Research, Ss. Cyril and Methodius University in Skopje, 2024)
Despite the multiple crises that have challenged the political leadership and slowed down the just energy transition process in the Republic of North Macedonia, the past few years marked significant milestones in the energy and climate sector. The country undertook serious international commitments for enhanced climate action and energy reforms with the submission of the Nationally Determined Contribution to the Paris Agreement and the endorsement of the Sofia Declaration on the Green Agenda for the Western Balkans in 2020 followed by an adoption of an action plan. The decarbonisation roadmap was underpinned with the preparation of the first integrated National Energy and Climate Plan and the agreement on the 2030 energy and climate targets at the 2022 Ministerial Council of the Energy Community. Some efforts to provide pathways to reach those targets have been made also on a national level. However, regardless of the attempts to encompass all the relevant policies and measures in the respective planning documents in a holistic manner, their implementation remains unsuccessful and the institutional approach is fragmented. The climate and energy portfolios continue to be divided among the competent authority in charge of the environment and the competent authority for energy, that lack the needed capacities deriving from the climate and energy legislation, even in the most restrictive sense of their understanding. The institutional mechanisms for operationalization of the broader concept of energy transition is completely missing, limited to the ad hoc coordination by different institutions. This arrangement does not deliver the needed institutional setup which would facilitate the systemic shift that the just energy transition prerequisites. This paper analyses the obligations deriving from the undertaken climate and energy commitments, the national documents transposing those obligations and their inter-relation with the competent institutions, as well as the capacities for their comprehensive planning, implementation and monitoring.
Keywords: NECP, Western Balkans Green Agenda, climate and energy targets